(25-3x)=(3x-17)

Simple and best practice solution for (25-3x)=(3x-17) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (25-3x)=(3x-17) equation:


Simplifying
(25 + -3x) = (3x + -17)

Remove parenthesis around (25 + -3x)
25 + -3x = (3x + -17)

Reorder the terms:
25 + -3x = (-17 + 3x)

Remove parenthesis around (-17 + 3x)
25 + -3x = -17 + 3x

Solving
25 + -3x = -17 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
25 + -3x + -3x = -17 + 3x + -3x

Combine like terms: -3x + -3x = -6x
25 + -6x = -17 + 3x + -3x

Combine like terms: 3x + -3x = 0
25 + -6x = -17 + 0
25 + -6x = -17

Add '-25' to each side of the equation.
25 + -25 + -6x = -17 + -25

Combine like terms: 25 + -25 = 0
0 + -6x = -17 + -25
-6x = -17 + -25

Combine like terms: -17 + -25 = -42
-6x = -42

Divide each side by '-6'.
x = 7

Simplifying
x = 7

See similar equations:

| 13-9x=101-37 | | 25-5y=4x-9y+13 | | 15x-90=180 | | (5x+13)=(9x-31) | | 5t/3-t/2=1 | | 5-x=2.8 | | 16=6s-20 | | 2(5-y)=2x+30 | | 3x+2-4y=1x-4 | | 4x-3(x+1)=2(x-1)-16 | | 4y-x=12 | | 3y+20=5 | | 2(y-3x)=16-12x | | 11=44x-11y | | 8u+21=45 | | (X-4)=3x+2 | | 3-5x+9=25 | | f(x)=5x^2+bx+c | | f(x)=-7x^2+28x+25 | | 6x=27y-3 | | (6*6)*(4*4*4)= | | 5(X-13)-7(6-X)+29=50-3(8-X) | | a+(a-8)=44 | | %.317=164 | | x^2+6.91830971e-7x-4e-8=0 | | x^2-3x/7x | | p+(-4)=1 | | 1a(105/(35/7)) | | 8x+8=9x-7 | | 3x+2x-5=x+7 | | 1/4×16 | | x^2+x-0.058=0 |

Equations solver categories